Impact of Redundancy and Line Extension on Short-Length Effect in Electromigration Reliability - Esposto, Simone; Ciofi, Ivan; Sisto, Giuliano; Croes, Kristof; Milojevic, Dragomir; Zahedmanesh, Houman (Proceedings of the IEEE International Interconnect Technology Conference, 2025)
This study investigates electromigration in a double-redundancy interconnect configuration, commonly found at standard-cell level in the power delivery networks, under downstream electron flow conditions, using both experiments and physics-based simulations. This work sheds light on the critical jL product, (jL) c , in presence of a parallel path. Due to double redundancy, for our samples coming from a 28nm commercial technology node, the critical current density j c was found to increase by 1.15-fold and 1.1-fold, for 5% and 20% R-shift failure criteria, respectively. The impact of line extension on (jL) c was also investigated. A 37% decrease in (jL) c was observed for a single line with a passive line extension acting as a sink, undermining the short-length effect, regardless of the failure criterion. For the same target lifetime, a 1.2-fold increase in maximum allowable current density, based on a 50% target failure percentile and 10 years lifetime criterion, was obtained when comparing the single and double redundancy configurations for 5% R-shift.